Pengaruh Kesehatan Mental Karyawan terhadap Niat Berhenti Bekerja Studi Kasus pada Mahasiswa/i STIE IBMI Medan - Andre Leonard Sirait; Anjelly Sitorus; Arpul Sianturi; Eka Kristian Hulu; Bayu Teta Pinem (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study investigates the correlation between mental health and turnover intention among working students at STIE IBMI Medan who fulfill dual roles as both students and employees. These individuals are particularly vulnerable to psychological stress arising from academic responsibilities and workplace demands. The objective of this research is to examine the influence of mental health on their tendency to resign from their jobs. An associative quantitative research method was adopted, with data collected through structured interviews involving 71 respondents. The analysis was conducted using simple linear regression via the SPSS application. The findings reveal that mental health has a significant negative effect on turnover intention, with a significance value of 0.001. This suggests that students who experience better mental health are less likely to consider leaving their jobs. The coefficient of determination (R Square) is 14.6%, indicating that mental health explains 14.6% of the variation in turnover intention. The remaining 85.4% may be attributed to other contributing factors, such as high work pressure from supervisors, poor work-life balance, financial stress, inflexible schedules, and lack of organizational support. The implication of these results is that efforts to support and maintain the psychological well-being of working students are essential for reducing employee turnover. Educational institutions and employers should collaborate to create supportive environments through counseling services, flexible scheduling, mental health awareness programs, and policies that accommodate the dual responsibilities of student workers. By addressing these mental health concerns, institutions can improve student performance and job retention simultaneously. This study highlights the importance of integrating mental health strategies in workforce and academic management, especially for populations that manage competing academic and professional obligations.